THE TEACHING MICROECONOMICS IN DIFFERENT COUNTRIES - Shvets, Yuriy Yu. (International Journal of Advanced Science and Technology, 2020)
Microeconomics is a subject that students know both as an economic one and as a business discipline. Studying microeconomic analysis is a difficult task for any student. It supposes the knowledge of a special terminology, of the free market principles and a fundamental understanding of decision-making processes. Most of domestic and foreign universities, microeconomics is considered as an axiomatic and abstract discipline related to the mathematical calculations and the studying of theoretical models. In this article it is proposed to consider not only the special aspects of teaching the microeconomics in different countries, but also the actual problems of teaching microeconomic analysis, including tools and recommendations for solving these problems.